Growth perfromance and mineral analysis of pleurotus ostreatus (Oyster Mushroom) cultivated on spent mushroom substrate mixed with rubber tree sawdust - Fathie, Ahmad Zakil; Raffizah, Mohd Isa; Mohd Shafiq, Mohd Sueb; Ruzinah, Isha (Elsevier Ltd, 2021)
Currently, Pleurotus ostreatus (oyster mushroom) is grown in Malaysia using rubber sawdust (RS). However, the strong demand and shortage of RS leads to rising prices, and this problem had been a big problem for mushroom growers in Malaysia. Therefore, an alternative medium for growing P. ostreatus needs exploration. This research was undertaken to evaluate the performance of yield and biological efficiency by using spent mushroom substrate (SMS) as an alternative for minimization of SMS wastes which is widely abundant in Malaysia. In this study, five different substrate composition with three replicates were prepared either in sole or in combination ratio 0.25 w/w, 0.5 w/w, 0.75 w/w and 1.0 w/w between SMS and RS. A substrate with only RS was used as a control experiment. All substrates were added 5% by weight of wheat bran and 1.5% by weight of calcium carbonate on a dry basis. The substrates' growth performance was recorded in terms of time for mycelial growth, time for first pinhead formation, the total yield of fresh mushroom and biological efficiency (BE). The height of the substrate was 15 cm along this study. The chemical properties such as pH value and moisture content of an alternative substrate were measured using a pH meter and a moisture content analyzer. Mineral analysis of the harvested mushrooms from 100% SMS and the control substrates were tested for their mineral values. It was found that the control substrate recorded the fastest mycelial growth of 24 days compared to 30 days for the 100% SMS. However, all the composition between RS and SMS substrates took about 29-35 days for the first pinhead formation. The control substrate (100% RS) gave the highest total average yield (g/bag), whereas the lowest total average yield is from 100% SMS substrate with yields of 159.67g/bag and 149.95g/bag and biological efficiencies of 53.22% and 49.98%, respectively. It is observed that the total average yield and biological efficiency (BE) increased with respect to the increasing amount of RS. In terms of mineral analysis, the fresh mushrooms from the 100% SMS substrate compared to the fresh mushrooms from the control substrate (100% RS) contained less 96.66% sodium (Na), less 54.36% magnesium (Mg), less 44.91% potassium (K) and less 94.38% calcium (Ca). The fresh mushroom from 100% RS and 100% SMS showed significantly lower values for almost all heavy metal of the mineral studies such as lead (Pb), cadmium (Cd) and arsenic (As). Hence, it can be proved that the SMS can be an excellent solution to address the disposal problem, whereas SMS can be an excellent medium for the cultivation of Pleurotus spp. when it is combined with the RS.